Energy and economic growth - Lolić Čipčić, Marina (Oeconomica Jadertina, 2023)
Without energy, there is no economic growth, therefore, for the smooth development of the economy, it is necessary to ensure sufficient amounts of energy at affordable prices. Increasingly frequent energy crises, by determining the availability and prices of energy, strongly influence the need to implement energy and economic measures and policies that will enable unhindered economic growth. Taking this into account, the task of scientists is to offer policy makers a clear theoretical and empirical concept of the relationship between energy and economic growth in order to adopt energy policies that will minimize the vulnerability of economies and enable sustainable economic growth and international competitiveness. The goal of this paper is to point out the contradictions between economic theory and existing empirical research on the interdependence of energy and economic growth. While growth theories completely ignore or, at best, marginalize the role of energy, research into the causality of economic growth and energy consumption is numerous, however, still inconclusive. The political implications of existing research are unsupported and should be taken with a great deal of caution. Only robust and consistent research results can serve as a solid basis for adopting adequate and timely economic and energy policy measures. Although the availability of data is one of the key limitations of the existing research, the authors should respect the multivariate framework in their future research, primarily through the consideration of energy prices in the models and use advanced econometric techniques.
Keywords: economic growth, energy, theories of growth, energy consumption, causality